Debt and life satisfaction: Unraveling the well-being divide among households in Abu Dhabi - Badri, Masood; Al Khaili, Mugheer; Dhaheri, Hamad Al; Yang, Guang; Albahar, Muna (Journal of Social Economics Research, 2025)
This study explores the impact of household debt on subjective well-being in Abu Dhabi, aiming to identify key factors that distinguish indebted from non-indebted individuals. Using data from 32,406 heads of households in the fourth cycle of the Abu Dhabi Quality of Life Survey, the analysis applies discriminant analysis to determine the well-being indicators that best differentiate between the two groups. ANOVA is also used to examine variations among indebted individuals by gender, nationality, age, education, and marital status. Eight indicators emerged as significant discriminators: income satisfaction, ability to meet essential expenses, perceived relative income, mental health, trust in others, family satisfaction, friends' satisfaction, and life satisfaction. Notably, subjective physical health did not emerge as a significant factor. The discriminant model achieved a classification accuracy of 89.55%. Further analysis revealed that women, younger individuals, Emiratis, those with lower education levels, and divorced or separated individuals reported greater vulnerability when in debt. The findings indicate that debt affects not only financial conditions but also emotional and relational aspects of life. The study highlights the need for integrated policy responses, including financial literacy programs, targeted mental health support, and inclusive social interventions to address the broader impacts of indebtedness in the Gulf context.